Low Total Lymphocyte Count as the Risk of Hospital Acquired Malnutrition in Children - Dian Sulistya Ekaputri; I Gusti Lanang Sidiartha; I Gusti Ayu Putu Eka Pratiwi (Cell and BioPharmaceutical Institute, 2021)
Background: Hospital Acquired Malnutrition (HAM) is characterized by inadequate nutritional therapy and the risk of developing malnutrition during the hospital stay. In clinical practice, there are many measurements to determine nutritional status. Total lymphocyte count (TLC) is associated with impaired function of immune system in malnutrition. The purpose of this study was to evaluate the prognostic value of TLC to the occurrence of HAM in pediatric patients.Materials and Methods: This an observational study with a prospective cohort design. Subjects were assessed for weight at the first day of hospitalization, then the subjects were followed until they were discharged. Body weight was re-measured on discharge to determine the presence or absence of HAM. This research was conducted at Sanglah Hospital from May-December 2019. Subjects who met the inclusion and exclusion criteria were enrolled in the study.Results: Among 120 subjects, 55 subjects or 45.8% were malnourished on admission. Subjects with a low TLC compared to a normal TLC had a 3.9-fold risk of experiencing hospital acquired malnutrition (95% Confidence Interval: 1.59 to 7.19, p=0.001). Subjects who had a low TLC had HAM of 61.8%, while subjects who had a normal TLC had HAM of 32.3%. In multivariate analysis, low TLC was the only risk factor for HAM in this research.Conclusion: This study proved that low TLC is the risk of HAM. Total lymphocyte count could be used as predictor of the risk of HAM in hospitalization children.Keywords: hospital malnutrition, total lymphocyte, children